Corporate social responsibility initiatives based company in the Republic of Moldova Moldcell SA - Stoian, Eugeniu (Інформація та соціум, 2024)
In recent years, the awareness of companies in Moldova of their role in social development has grown significantly, evidenced by the establishment of the Global Compact Moldova (GPM) network and the joining of a growing number of companies to it. Although philanthropy is well rooted in Moldovan business culture, the adoption and implementation of Corporate Social Responsibility (CSR) practices is still in its infancy. The traditional relationship between the state and the private sector, where companies are often ‘asked’ to donate, contributes to this situation, with companies perceiving philanthropy as an unofficial ‘tax’. The case study on Moldcell shows how the company has integrated CSR values into its strategy, contributing to the development of information infrastructure and supporting social, cultural and environmental phenomena in Moldova. Moldcell, a member of the Global Compact Network in Moldova since 2006, promotes sustainable development and believesthat ethical and transparent businessisthe key to the prosperity of the sector and the country.